Clinical and onychoscopic characteristics of subungual glomus tumor: a cross‐sectional study. (17th December 2020) - Grover, Chander; Jayasree, Puravoor; Kaliyadan, Feroze
Abstract: Background: Subungual glomus tumor is a relatively uncommon entity with varied clinical presentations which may lead to diagnostic delays. Onychoscopy can be used as an evaluation tool in routine evaluation of glomus tumors. Objectives and methods: With an aim to characterize the onychoscopic features of subungual glomus tumors, we analyzed 15 cases presenting over 3 years, in this observational study. The clinical, onychoscopic, radiological, and operative findings in these patients were evaluated and correlated depending on the location and extent of the lesions. Results: All 15 patients (11 female and 4 male) had pain as the presenting symptom and fulfilled the classic triad of paroxysmal pain, cold sensitivity, and positive Love's pin test. Clinical nail plate findings included onycholysis, onychorrhexis with distal splitting, and onychoschizia, while nail bed and matrix findings included localized erythematous and bluish patches, longitudinal erythema, and altered lunula. Onychoscopy corroborated the clinical findings and revealed a more extensive area of involvement in five cases. Definitive onychoscopy findings included a localized structureless erythema interspersed with bluish and patchy whitish areas (five cases of nail bed and six nail matrix tumors) and a "candy‐cane appearance" (six cases, all large and lobulated nail matrix tumors). MRI reported the tumor in 13 cases, while two nail matrix tumors were missed. Transungual excision revealed tumors larger in size than predicted by MRI. The presence of candy‐cane appearance was consistent with lobulated matrix tumors. Conclusion: Onychoscopy improves the intraoperative detection of location and extent of subungual glomus tumors. Nail bed and nail matrix glomus tumors can have distinctive onychoscopic features that may help in better surgical planning.